Normative Juridical Study of Regulatory Urgency Use of Local Labor in the Regions: Normative Juridical Study of Regulatory Urgency Use of Local Labor in the Regions - Simarmata, Jorawati (Jurnal Ketenagakerjaan, 2024)
Indonesia, in the context of "advancing general welfare" as mandated by the preamble to the 1945 Constitution, is responsible for responding to employment problems through national development. The government directs various regulations in the field of employment to regulate "Indonesian workers" and/or the use of "foreign workers" in the context of equal and fair employment opportunities. However, the phenomenon is that local governments see a legal vacuum (recht vacuum) to regulate local/regional workers or in other words, "local workers". Consequence, many regions in Indonesia have issued regulations that involve "the use of local labor" in the form of regional regulations or regent/mayor regulations. In this normative juridical study the problem is formulated: (i) How is the use of local labor regulated in the regions based on statutory regulations? (ii) What is the urgency of regulating the use of local labor in the regions? In principle, this article aims to answer these two things. First, to find out and analyze legal regulations related to the use of local workers in the regions. Second, to formulate the urgency of regulating the use of local labor in the regions. In this study, it was found that the regulation of the use of local workers in the regions is not an order from existing laws and regulations in Indonesia and is not an authority that implicitly regulates local workers, but rather a regional government policy to accommodate regional conditions related to the problem of employment opportunities for workers-local work. The obligation to provide opportunities for local workers and residents around the company does not mean it is discriminatory because it is still open while prioritizing the principle of professionalism according to the prospective workers' standards of ability and skills.